CORPORATE REPUTATION AND ORGANIZATIONAL LEGITIMACY - Luiza ION (DOMNIȘORU) (Association of Social and Educational Innovation, 2024)
Across the last four decades, a vast scientific literature has analyzed the relationship between corporate reputation and organizational legitimacy (Cornelissen, 2004; Deephouse & Suchman, 2008; Tost, 2011; Bartlett et al., 2013; Bitektine & Haack, 2015) to highlight differences and similarities. This study aimed to analyze the scientific literature about organizational legitimacy and corporate reputation, employing a methodological design in three steps: literature refining through a systematic literature review, corpus selection, and conceptual universe delimitation. The systematic review was performed across the Web of Science and Scopus databases. The search equations were organizational reputation AND legit (legitimation/ legitimacy) within domains related to communications, sociology and business management. The final sample was established after filtering the queries by English language, open-access articles, and texts having both terms present in abstracts or keywords (n=71 articles) for the final corpus selected articles being cited at least once (n=57). A content analysis using mixed methods (quantitative and qualitative) of the selected corpus and Computer-Assisted Qualitative Data Analysis Software (CAQDAS) Leximancer and Atlas.ti completed the systematic review. The scientific literature published between 1994 and 2022 on organizational legitimacy and corporate reputation concepts showed that the theory of legitimacy and the sociopolitical approach were the prevailing themes. The most commonly used research method was qualitative (case studies, discourse analysis, in depth or directed interviews). Companies and profitable organizations associate reputation and legitimacy through social norms and ideological constructs (Palazzo & Scherer, 2006). Organizations invest in communication efforts, such as social media (Twitter, Instagram), business and sustainability reporting, and stakeholder communication management, to strengthen the relationship between these intangible assets (Rao, 1994; Sorenson, 2014; Martinez et al, 2018; Del-Castillo-Feito et al., 2020). The findings of this study can bring important insights for future research on the strategies used by the profitable organizations to build their reputation and self-representation on social media through discursive legitimation practices.